The Role Of International Financial Reporting Standards (IFRS) In Enhancing The Quality Of Financial Reporting Applied Research In a Sample Of Iraqi Banks Listed On The Iraq Stock Exchange - Saddam Catea Hashim (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
The aim of the research is to show the importance of applying IFRS standards at the international and local levels in Iraqi banks and its reflection. This research used statistical methods and indicators, as the data were collected through the distribution of questionnaires to a sample of international development banks, and Gulf commercial banks, to accountants and auditors working in Iraq, where they were distributed to (226) participants and analyzed using SPSS v 26 and Amos v 26, as well as a study comparing the impact of the application of IFRS-9 before and after by analyzing the financial statements of the above banks. The research included the study of several topics, including an overview of IFRS standards and the quality of financial reports, the definition of international financial reporting standards, the objectives of financial reports prepared for public use, the importance of IFRS, the quality of financial reports, the factors affecting the quality of financial reports, the importance of IFRS standards, the factors affecting the quality of financial reports, the challenges faced by banks in preparing financial reports, the application of IFRS standards, the impact on the performance of banks, the application of IFRS standards, the fair presentation of the financial position, the application of IFRS standards and the presentation of cash flows to banks, and the reality of adopting IFRS standards in Iraqi banks. The research concluded that the presence of interest of Iraqi banks in the application of financial reporting standards in order to enhance the quality of financial reporting, that the level of impact of International Financial Reporting Standards (IFRS) in enhancing the qualitative characteristics of accounting information among Iraqi banks (the research sample), all of which increased the application of IFRS, reflected positively on the qualitative characteristics of accounting information. The research contributes to financial institutions such as banks and banks as a means of providing external users, investors and at all levels with the financial data and information necessary to make rational and correct decisions after the application of IFRS standards.